Perencanaan Palang Pembatas sebagai Pengganti Highcheck Sensors pada Baggage Handling System di Check-In Area Terminal Domestik Bandar Udara I Gusti Ngurah Rai – Bali - Kurniawanto, Hari; Suwono, Niedya Inten; Samosir, Jesicha Christin; Nugraha, I Made Krisna Adi; Sayekti, Diah Ayu; Maharani, Putu Ayu Devina (Jurnal Teknik Mekanikal Bandar Udara, 2023)
Technology continues to experience developments that are members of the industry damcak for aviation in the world and Indonesia. The standard of ability of the shaving workforce engaged in the aviation industry will of course be disputed because of the scrambling development. To be able to compete in an increasingly stringent world of work, it is not only a theory that is relied upon but also a skill and expertise. One technology that continues to develop is the Baggage Handling System ( BHS ) which has a function to move passenger baggage from one place to another continuously and continuously. Problems found in the Baggage Handling System ( BHS ) domestic chest terminal, the presence of ducting devices damaged by friction and/or collisions with passenger luggage/baggage. The existence of chest damage to the ducting tool is feared in the absence of a high check sensor ( height sensor ) chest BHS Domestic Terminal in the departure area ( departure ). A barrier is planned as a substitute for the domestic terminal breast height check sensor. In the study the distance that was too close between the conveyor and the ducting turned out to cause chest damage to the ducting tool. A short and better thing than making a barrier with its safety components. This study will be discussed thoroughly about the Baggage Handling System along with problems and how to overcome them.